PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN IPS SD KELAS VI MELALUI PENDEKATAN PEMBELAJARAN SAINTIFIK - Asih, Nofi Nuristia (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
The purpose of this research is to develop a plan for implementing Ips VI SD learning through a scientific learning approach. The scientific approach is an integrated learning approach that can be applied in a Learning Implementation Plan because the scientific approach uses a scientific and inquiry approach where students are directed and guided in activities to observe, ask, try, reason and build networks or communicate to disseminate the learning outcomes obtained by this in accordance with the main learning experience of the 2013 Curriculum. The research subjects themselves were students of class VI SD Negeri 2 Merak Batin, South Lampung. And in this case the chosen theme is Theme 5 Entrepreneurship, Sub-Theme 2 Businesses Around Me, learning to one. The method used in data study is a qualitative method with descriptive research type. The results of this study are in the form of data showing that researchers can develop a learning implementation plan by applying a scientific learning approach.